A Durable Laparoscopic Technique for the Repair of Large Paraesophageal Hernias. Issue 10 (October 2016) - Reynolds, Jessica L.; Zehetner, Joerg; Bildzukewicz, Nikolai; Katkhouda, Namir; Lipham, John C.
Laparoscopic repair of large paraesophageal hernias has been challenging due to high recurrence rates with primary repair and complications associated with the use of nonabsorbable mesh to reinforce the hiatus. The aim of our study was to evaluate the recurrence rate over time and mesh-related complications using an absorbable polyglactin mesh secured with Bioglue to reinforce the hiatus after laparoscopic repair of large paraesophageal hernias. There were 190 patients who met inclusion criteria from June 2006 to June 2014. Follow-up was routinely performed at 1-year intervals, including endoscopy and/or video esophagram, and the gastroesophageal reflux disease health-related quality of life questionnaire. Mean follow-up was 21 months (3–88). There were no incidences of mesh erosion. Recurrence was detected in 17 patients (15.3%), with a median time to recurrence of 23 months (8–67). Recurrence rate was estimated with the Kaplan-Meier method to be 2.9 ± 1.6 per cent, 11.6 ± 3.7 per cent, 22.4 ± 5.6 per cent, 25.1 ± 6.0 per cent, and 29.5 ± 7.9 per cent at 12, 24, 36, 48, and 60 months, respectively. The mean gastroesophageal reflux disease health-related quality of life was 2 in patients both with and without recurrence. Laparoscopic intrathoracic stomach repair using absorbable polyglactin mesh and Bioglue for crural reinforcement is effective, safe, and durable. The rate of recurrence plateaus over time with the majority of recurrences being small to moderate asymptomatic hernias.